Exploration of new water stable proton-conducting materials in an amino acid-templated metal phosphate system. Issue 3 (11th December 2017) - Shi, Jingyu; Wang, Kangcai; Li, Jing; Zeng, Hongmei; Zhang, Qinghua; Lin, Zhien
Abstract : Presented here is the first example of an amino acid-templated metal phosphate with a three-dimensional structure, which shows excellent water stability and a high proton conductivity at room temperature under 98% relative humidity. Abstract : Two new metal phosphates, namely, Zn(HPO4 )(dl -C3 H7 NO2 ) (SCU-4) and In(HPO4 )(H2 PO4 )(dl -C3 H7 NO2 ) (SCU-12), were prepared in the presence of the amino acidl -alanine. SCU-4 has a ladderlike structure with edge-sharing 4-rings. SCU-12 represents the first example of a three-dimensional metal phosphate templated by an amino acid. It remains stable in boiling water and shows a high proton conductivity at room temperature under 98% relative humidity.